Pengembangan Kewirausahaan dan Transformasi Digital terhadap Penguatan Ekonomi Daerah: Analisis Structural Equation Modeling dengan Peran Mediasi Kinerja UMKM di Sulawesi Selatan Periode 2019–2025 - Wahyuni; Mochammad Fadhil Abdullah; Nurjannah (PT Bukuloka Literasi Bangsa, 2026)
This study examines the effects of entrepreneurship development and digital transformation on regional economic strengthening, with MSME performance as a mediating variable in South Sulawesi during the 2019–2025 period. Using a quantitative approach data were collected from MSME actors and analyzed using Structural Equation Modeling (SEM).. The findings reveal that entrepreneurship development and digital transformation significantly enhance MSME performance. In turn, MSME performance positively contributes to regional economic strengthening and mediates the relationship between the independent variables and regional economic outcomes. Both direct and indirect effects are statistically significant, indicating the strategic role of MSMEs in linking entrepreneurship and digitalization to regional economic resilience. This study highlights the importance of integrated policies that promote entrepreneurial capacity and digital adoption to achieve sustainable regional economic strengthening. Keywords: entrepreneurship development; digital transformation; MSME performance; regional economic strengthening; SEM